China’s changing perspective on the WTO: From aspiration, assimilation to alienation - GAO, Henry S. (Institutional Knowledge at Singapore Management University, 2022)
Since its accession to the WTO twenty years ago, China's image has shifted from a good student aspiring to assimilate itself into the multilateral trading system to one that is increasingly alienated from key WTO principles. How has China's perspective on WTO been evolving? What are the reasons behind China's changing perspective? This paper answers these questions from the Chinese perspective with a comprehensive analysis of the key moments in China's first two decades in the WTO, followed by practical suggestions on how to engage China more constructively in the WTO and beyond.